Some Judges' Considerations in Deciding Marriage Dispensation Cases - M Nur Kholis; Moh. Muhibbin (International Journal of Social Service and Research, 2023)
There are many reasons behind the occurrence of early marriages in Rembang, including the factor of being pregnant first with the background of uncontrolled social relations, so that the parents of both parties agreed and submitted a request for dispensation to the Rembang Religious Court to be able to get a decision from the Judge allowing them to marry in Rembang. Age that does not yet meet the applicable laws in Indonesia. This research was carried out using sampling, analysis, primary, secondary and tertiary data techniques where the research was carried out by interviewing, reviewing, collecting data, and searching for data related to the problem, which was made into a theory in this writing. And also this research was obtained from a study (Library research) or Normative. From the collected data it was analyzed using the Empirical method. So the resulting research shows that basically early marriages are carried out because there are things that parents feel require them to marry their children at an age that does not meet the provisions of the law. There are many factors behind the existence of early marriage in Rembang, which according to researchers, all of these reasons lead to undesirable things, if a person is not immediately married.